The form factor and the density distribution of the 4He nucleus using the Morse potential - Ypsilantis, K.; Dimitrova, S.; Koutroulos, C. G.; Grypeos, M. E.; Antonov, A. (HNPS Advances in Nuclear Physics, 2020)
The form factor and the density distribution of the He nucleus are calculated approximately using the Morse single-particle potential. The parameters are determined by fitting the theoretical charge form factor to the corresponding experimental data of the elastic electron scattering by 4He, which are extended to large values of the momentum transfer. The corrections due to the center of mass motion (in the fixed center of mass approach) and of the finite proton size have been taken into account. The calculations can be performed partly analytically and the results show a considerable im- provement with respect to those obtained with the oscillator shell model.